2011
DOI: 10.5588/ijtld.10.0195
|View full text |Cite
|
Sign up to set email alerts
|

Does solid culture for tuberculosis influence clinical decision making in India?

Abstract: Using solid culture, 150 cultures need to be tested for one treatment modification and 30 for DST. The cost of the widespread application of culture will need to be balanced against its impact on treatment decisions in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
1
9
1
Order By: Relevance
“…Our analysis suggests that enhanced laboratory identification using solid culture media and blood culture averted, at most, eight additional TB deaths implying that solid TB culture, even if routinely available, may offer only modest gains, a conclusion also reported from India [37]. Prompt initiation of TB treatment would be better supported through improved access to rapid point-of-care diagnostics for TB but in their absence empiric TB treatment warrants careful consideration, particularly among patients with the risk factors for mortality observed in this study.…”
Section: Discussionsupporting
confidence: 62%
“…Our analysis suggests that enhanced laboratory identification using solid culture media and blood culture averted, at most, eight additional TB deaths implying that solid TB culture, even if routinely available, may offer only modest gains, a conclusion also reported from India [37]. Prompt initiation of TB treatment would be better supported through improved access to rapid point-of-care diagnostics for TB but in their absence empiric TB treatment warrants careful consideration, particularly among patients with the risk factors for mortality observed in this study.…”
Section: Discussionsupporting
confidence: 62%
“…We were unable to compute numeric differences in the estimates of meta-analyses versus package inserts because pooling of data was often not possible due to heterogeneity between studies and the presence of several meta-analyses that included partially overlapping studies. We acknowledge that real-world performance of tests, especially when tests are scaled up in public health programs, may be worse than those reported in research studies, including meta-analyses (27). Thus, the real gap between package insert estimates and real-world performance may be even wider than what we document here.…”
contrasting
confidence: 50%
“…In addition to smear, IGRA, and Xpert MTB/RIF, we also examined a scenario including mycobacterial culture. We do not present those findings in detail, however, as research has shown that culture results have limited impact on physician’s treatment decisions in India [ 19 ]. We included the effects of multi-drug resistant TB (MDR-TB) on each these diagnostic scenarios, assuming an MDR-TB prevalence of 2.1% among all newly diagnosed Indian adult TB cases [ 20 ], and examined the costs and consequences of diagnosing and treating MDR-TB for the Xpert arm (as, unlike smear or IGRA, Xpert is capable of diagnosing resistance to rifampin, a proxy measure for MDR-TB).…”
Section: Methodsmentioning
confidence: 96%